1982
DOI: 10.1128/aem.44.2.428-434.1982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on growth rates of rumen amylolytic and lactilytic bacteria

Abstract: The relationship between the pH of the medium and specific growth rates, in well-buffered media at 38.5 degrees C, was determined for three strains of Butyrivibrio fibrisolvens and for one strain each of Streptococcus bovis, Selenomonas ruminantium subsp. lactilytica. Megasphaera elsdenii, Veillonella alcalescens, and Propionibacterium acnes. The pH optima for growth were between 6.1 and 6.6 for all six species, and the upper pH limits were between 7.3 and 7.8. The lower limit pH values for growth on glucose w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
36
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 15 publications
7
36
1
Order By: Relevance
“…The shift in fermentation end-product production and consequently amelioration of pH decline observed could be attributed to increased activity of lactate-utilizing bacteria or a change in the amylolytic bacteria guild, leading to slower rates of starch degradation. When the pH drops below 5Á0, the growth of lactate-utilizing bacteria is inhibited and lactic acid accumulates (Therion et al 1982). Lactate-utilizing bacteria were not enumerated in the current study.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The shift in fermentation end-product production and consequently amelioration of pH decline observed could be attributed to increased activity of lactate-utilizing bacteria or a change in the amylolytic bacteria guild, leading to slower rates of starch degradation. When the pH drops below 5Á0, the growth of lactate-utilizing bacteria is inhibited and lactic acid accumulates (Therion et al 1982). Lactate-utilizing bacteria were not enumerated in the current study.…”
Section: Discussionmentioning
confidence: 68%
“…However, when lactic acid production exceeds the capacity of metabolism by lactate-utilizing bacteria, lactic acid can accumulate in the rumen . Lactic acid accumulation leads to a decline in rumen pH and inhibition of the normal rumen microflora including lactate-utilizing bacteria (pH <5Á0), causing a decrease in other fermentation end-products, further lactic acid accumulation and pH decline (Huber 1976;Slyter 1976;Therion et al 1982). Notably, resident cellulolytic bacteria cannot tolerate a pH <6Á0, leading to decreases in viable numbers and consequent fibre digestibility (in situ studies: 20-25% reduction in fibre digestibility; Shi and Weimer 1992;Plaizier et al 2001;Krajcarski-Hunt et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Average ruminal fluid pH was below 6.2 for heifers fed 3335 for approximately 2 h; however, average ruminal fluid pH did not fall below 6.2 for 3223 for any amount of time. Researchers have suggested that ruminal fluid pH less than 6.2 will decrease fiber digestion through decreased growth and activity of fibrolytic bacteria (Therion et al, 1982;Grant and Mertens, 1992). Although the overall mean pH was above this level, increased time below pH 6.2 for heifers fed 3335 may have affected ruminal fiber digestion.…”
Section: Ruminal Fluid Characteristicsmentioning
confidence: 99%
“…Numerous studies have reported the approximate pH ranges (Buchanan & Klawitter, 1992;Cole, Jones, & Holyoak, 1990;FDA, 2015;ICMSF, 1980;Presser et al, 1997;Russell & Dombrowski, 1980;Therion, Kistner, & Kornelius, 1982) and temperature ranges (Augustin, Rosso, & Carlier, 2000;Doyle, Mazzotta, Wang, Wiseman, & Scott, 2001;FDA, 2011;ICMSF, 1996;Lund, Baird-Parker, & Gould, 2000;Nguyen, 2006;Patchett, Watson, Fernandez, & Kroll, 1996) that limit growth of bacterial pathogens. However, several scientists indicated tolerance of foodborne pathogens for non-optimal pH and temperature (Gandhi & Chikindas, 2007;Glass, Loeffelholz, Ford, & Doyle, 1992;Shachar & Yaron, 2006), survival of foodborne pathogens in non-optimal pH and temperature (Rocourt & Cossart, 1997;Zhao & Doyle, 1994), and resistance to the lethal effects of very low pH (Leyer, Wang, & Johnson, 1995).…”
mentioning
confidence: 99%